2022
DOI: 10.1177/13623613221098237
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake and adequacy in children with autism spectrum disorder: EPINED epidemiological study

Abstract: This article assesses nutritional intake and adequacy in children with autism spectrum disorder (ASD), subdiagnostic autistic symptoms and children with typical development (TD). In total, 77 children diagnosed with ASD, 40 with subdiagnostic autistic symptoms and 333 children with TD were assessed. A validated food frequency questionnaire was used. Very few nutritional differences were found between ASD and TD groups. Preschool children with ASD and subdiagnostic autistic symptoms had slightly lower intake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…It has been suggested that children with ASD experience many vitamin and mineral deficiencies as a result of their poor intake of daily energy sources, carbohydrates, fats, and protein, as well as their extremely permeable intestines and highly selective diets. 22, 23 Another study found that children with autism have a higher rate of food rejection compared to healthy children, resulting in nutritional inadequacies caused by their limited dietary preferences. 24 In addition, nutritional treatments applied to prevent the symptoms of autism, such as glutenfree and casein-free diets, may cause vitamin and mineral deficiencies.…”
Section: Nutritional Status In Autism Spectrum Disordermentioning
confidence: 99%
“…It has been suggested that children with ASD experience many vitamin and mineral deficiencies as a result of their poor intake of daily energy sources, carbohydrates, fats, and protein, as well as their extremely permeable intestines and highly selective diets. 22, 23 Another study found that children with autism have a higher rate of food rejection compared to healthy children, resulting in nutritional inadequacies caused by their limited dietary preferences. 24 In addition, nutritional treatments applied to prevent the symptoms of autism, such as glutenfree and casein-free diets, may cause vitamin and mineral deficiencies.…”
Section: Nutritional Status In Autism Spectrum Disordermentioning
confidence: 99%
“…On the other hand, Bandini et al ( 6 ) showed that some aspects of eating problems, such as food refusal or frequency of problematic mealtime behaviors (e.g., tantrums about food), improved over a longer time period from childhood to adolescence (6.8 to 13.2 years, n = 18). Eating problems may predispose children with diagnosed and even subclinical ASD symptoms to poor diet quality ( 7 ) and suboptimal nutritional intake ( 8 ). While eating problems are presumed to be an epiphenomenon of ASD, eating problems may also modulate diet to influence the severity of ASD-associated symptoms ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%